Indium-MOF as Multifunctional Promoter to Remove Ionic Conductivity and Electrochemical Stability Constraints on Fluoropolymer Electrolytes for All-Solid-State Lithium Metal Battery - Xiong Xiong Liu; Long Pan; Haotian Zhang; Cancan Liu; Mufan Cao; Min Gao; Yuan Zhang; Zeyuan Xu; Yaping Wang; ZhengMing Sun (Nano-Micro Letters)
Highlights Indium-based metal–organic framework (In-MOF) is proposed as a multifunctional promoter to create poly(vinylidene fluoride–hexafluoropropylene) (PVH)/In-MOF (PVH-IM) composite solid polymer electrolyte, synchronously achieving a high ionic conductivity of 1.23 × 10−3 S cm−1 and excellent electrochemical stability against Li anodes. In-MOF not only can adsorb and convert free residual solvents into bonded states to prevent their side reactions with Li anodes, but also induce inorganic-rich solid electrolyte interphase layers to prevent PVH from reacting with lithium anodes and promote uniform lithium deposition without dendrite growths. The Li|PVH-IM|Li symmetric cells maintain stable cycling for 5550 h at the current density of 0.2 mA cm−2. In addition, all-solid-state LFP|PVH-IM|Li full cells deliver a significant capacity retention of 80.0% at a rate of 0.5C after 280 cycles at 25 °C.